Dendritic Cells Transduced with Single Immunoglobulin IL-1-Related Receptor Exhibit Immature Properties and Prolong Islet Allograft Survival - Xue, Zhicheng; Zhang, Xuzhi; Chen, Maogen; Lu, Xinjun; Deng, Ronghai; Ma, Yi (Frontiers in Immunology, 2017)
Members of TLR/IL-1R (TIR) superfamily mediate maturation of dendritic cells (DCs) and initiate immune response in transplanted organs. In this study, we tested the hypothesis that TIR8, also known as single Ig IL-1 receptor-related molecule (SIGIRR), refrain DCs from maturation and induce immune tolerance of transplant organ. DCs were transduced with the recombinant adenovirus Ad5F35 to highly express SIGIRR (DC-SIGIRR), then injected to murine recipient before islet transplantation. It revealed that DCs transduced with SIGIRR had low expression of major histocompatibility and costimulatory molecules along with strong phagocytic ability in vitro assay. The data demonstrated that recipients treated with DC-SIGIRR had satisfying islet allograft function and long survival times, with an increase of Treg and reduction of Th17 in both spleen and draining lymph nodes in vivo. Therefore, genetic modification of SIGIRR inhibits DC activation and maturation, affects differentiation of T cell subsets, protects allograft biological function, and prolongs graft survival.